Financial Prospect to The Application of High Rate Water Treatment Plant System - hajit, Mo (Teknik Lingkungan Universitas Islam Indonesia, 2010)
The High Rate Water Treatment Plant (HR-WTP) system, which is inexpensive, effective and efficient, hasbeen developed to reduce the common operational problems, and also as an alternative for thedevelopment of water treatment plant systems capacity in Indonesia.Implementation of HR-WTP system in up-rating of the Dekeng-WTP system at PDAM Kota Bogor provedsuccessful in increasing the plant capacity from its original of 500 Lps to more than 1200 Lps. Theperformance of the WTP system was also significantly improved from poor performance to very goodperformance.The investment cost for up-rating proved competitive when compared to alternatively constructing a newWTP system with an equivalent capacity and performance. Application of HR-WTP systems for thedevelopment of WTP system in Indonesia, i.e. rehabilitation, up-grading, and up-rating, as well asconstruction of a new WTP system, is expected to bring technical, financial, and economic benefits.This new approach might be an innovative solution to the challenge of Millennium Development Goals inWater Supply Sector in Indonesia, where an additional capacity of ca 150,000 Lps should be developedwithin a 15 years period with an estimated budget of US 1.5 billions. This budget might be reduced toless than 50% through the application of the HR-WTP system.Keywords: loading rate, filtration rate, conventional system, high rate system